The Politics of the Hero's Journey: A Narratology of American Special Education Textbooks - Elise Assaf; Jennifer James; Scot Danforth (Disability Studies Quarterly, 2021)
This paper explores introduction to special education textbooks in order to illuminate how they portray the social and political work of special educators, especially in relation to disabled students and adults. This study analyzed five leading special education textbooks used in university teacher education programs using traditional methods of discourse analysis, including line-by-line coding and language-in-use with valuation. The analysis and coding tracked story plot components and characters associated with five phases evident in the narrative structure of a hero's journey: (1) the call to adventure, (2) supernatural aid, (3) threshold guardians, (4) trials and tribulations, and (5) the return. Discussions of the findings illustrate the problematic ways in which the textbooks create a heroic narrative of past and current elements tied to the field of special education.
Keywords: special education; narratology; narrative structure; critical discourse analysis; hero' s journey; inclusion; special education textbooks